PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Melati, Anggraeni Eka; Sunardi, Sunardi; Trapsilasiswi, Dinawati (Kadikma, 2017)
Abstract. The purpose of this research is to describe the influence of learning using Indonesian Realistic Mathematics Education and conventional learning to athematical communication ability of students, and to know the difference between students who have high abilityand low ability to the mathematical communication abilities. Before determining the sample of population will be tested for normality and homogeneity. After the test have done, we get VII-H class and VII-I class as a control class and experiment class. Data collection was obtained by giving the test in experiment class and control class in the form of pre test and post test which have passed validity test. The results of data analysis is using independent sample t test, it show that tcount> ttable (1,995 > 1,933) and p-value (0,047 < 0,05) then H0 is refused. So there is an influence of learning using Indonesian Realistic Mathematics Education and conventional learning to mathematical communication ability of students. To knowing whether there is an increase of mathematical communication ability on experiment class used paired sample test and be obtained significant value of 0,000. Because the significant value is 0,000 < 0,05 then there is increase mathematical communication ability of students. Number influence of variable is obtained value 21,809 with positive sign, it means that if there is no Indonesian realistic mathematics education approach then the value of mathematical communication ability is 21,809.Number of correlation coefficient (r) is 2,255, it means that the correlation between Indonesian realistic mathematics education variable and mathematics communication ability of students is positive. The results data analysis of the second hypothesis is using independent sample t test, it show that > (2,399 > 1,933) andp-value (0,022 < 0,05) then H0 is refused. It indicates that group of students who have high ability have significant difference of the result mathematical communication ability of students. Keywords: mathematical communication, Indonesian realistic mathematics education approach.